The long white - Dilworth, Sharon (Iowa short fiction award., 1988)
In the sparsely settled hills of Michigan's Upper Peninsula, winter's toughness is matched only by the animosity and affection of its inhabitants for each other and for the land that unnerves them. In The Long White, Sharon Dilworth evokes a place dominated by two great lakes whose power and ferocity influence the lives of every inhabitant. The particularities of place and character come together with the clarity and exactitude of a fresh snowfall that both veils and illuminates a landscape.